Does height matter for earnings?: evidence from Russia - Ibragimova, Nargiza; Salahodjaev, Raufhon (Journal of biosocial science, 2020)
This study explores the link between height and earnings, using data from the Russian Longitudinal Monitoring Survey for the year 2015 (24th wave). The dependent variable was average monthly income and the key independent variable was self-reported height, measured in centimetres. The empirical model also included a rich vector of personal and job-related factors that have been shown to be associated with earnings in the relevant literature. Sequential multiple regression and one-way analyses of variance (ANOVA) were used to analyse the data. The results suggest that height is a significant predictor of earnings in Russia. The results were found to be robust for a set of controls and tests.
Gesehen am 24.02.2021